Does an Immersive, Technology-Enhanced Course Design Improve Nursing Student's Learning Experience and Pathophysiology Exam Results? - Dr. Karole Hogarth, Dr. Liz Ditzel (International Journal of Innovative Research in Medical Science, 2017)
Aim: This study evaluated the impact of an innovative technology-enhanced immersive approach to course design on second-year undergraduate nursing student’s learning experience and exam performance. Background: Two case-based learning modules using LabTutor® an online learning programme were developed to help students link their pathophysiology knowledge with clinical assessment (both taught in theory courses) and clinical practice skills using a high-fidelity simulation manikin and structured debrief. Methods: This research was conducted in a New Zealand School of Nursing over the 2014 academic year. Qualitative data was gathered using focus groups and coded from responses to open-ended questions gathered by an online survey. Quantitative data from mid-year examination marks were analysed at the end of the academic year. Results: Participants were second year undergraduate nursing students (N=111): Focus group interviewees (n=71, 64%) and survey respondents (n=82, 73%). Qualitative data indicated that elements of the immersive learning model worked together to reinforce learning. Students found the case studies, particularly the video, tutorial, notes and supporting medical documents highly valuable. Both case studies effectively enhanced students’ understanding of pathophysiology. Quantitative analyses showed that the immersive learning group of students (n=52) achieved higher exam marks in pathophysiology. Conclusion: These findings indicate that a technology-enhanced immersive learning approach using case studies, Labtutor® and high-fidelity simulation enhances the nurse’s understanding of pathophysiology.